Two Mutations in Surfactant Protein C Gene Associated with Neonatal Respiratory Distress - Anna Tarocco; Elisa Ballardini; Maria Raffaella Contiero; Giampaolo Garani; Silvia Fanaro (Case Reports in Pediatrics)
Multiple mutations of surfactant genes causing surfactant dysfunction have been described. Surfactant protein C (SP-C) deficiency is associated with variable clinical manifestations ranging from neonatal respiratory distress syndrome to lethal lung disease. We present an extremely low birth weight male infant with an unusual course of respiratory distress syndrome associated with two mutations in the SFTPC gene: C43-7G>A and 12T>A. He required mechanical ventilation for 26 days and was treated with 5 subsequent doses of surfactant with temporary and short-term efficacy. He was discharged at 37 weeks of postconceptional age without any respiratory support. During the first 16 months of life he developed five respiratory infections that did not require hospitalization. Conclusion. This mild course in our patient with two mutations is peculiar because the outcome in patients with a single SFTPC mutation is usually poor.